Alumni Loyalty in Higher Education (Case of Three Private University Alumni of BA Business Administration Programs) - Buchashvili, Goderdzi; Jikia, Nino; Mesiridze, Irma (Journal of Education in Black Sea Region, 2019)
In the 21st century, the increasing need for enhancing the quality of education in higher educational institutions has caught a high interest of researchers in studying the influence of quality of educational services on students’ satisfaction and graduates’ loyalty. Taking into account the purpose of the study, the questionnaire used in it contains predictive and descriptive questions. The research describes different factors, such as service quality, facilities, administrative staff helpfulness, university location, and academic staff professionalism impact on the level of alumni loyalty. The information has been obtained at three private universities in Georgia. Research results were gathered for comparative analysis. The research variable, in this case factors affecting the level of loyalty, should be paid attention to, in order to gain a high level of alumni loyalty.